2008
DOI: 10.1089/apc.2008.0093
|View full text |Cite
|
Sign up to set email alerts
|

Structures of Care in the Clinics of the HIV Research Network

Abstract: As the HIV epidemic has evolved to become a chronic, treatable condition the focus of HIV care has shifted from the inpatient to the outpatient arena. The optimal structure of HIV care in the outpatient setting is unknown. Using the HIV Research Network (HIVRN), a federally sponsored consortium of 21 sites that provide care to HIV-infected individuals, this study attempted to: (1) document key features of the organization of care in HIVRN adult clinics and (2) estimate variability among clinics in these parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…A similar study carried out with 21 American sites showed an average appointment time of 20 minutes, varying between 15 and 40, for this type of appointment. 16 It is probable that, for some sites, the main problem is a lack of doctors, given the shortages and poor distribution of this professional, especially in public health services. Moreover, "squeezing in" patients who do not have appointments may contribute to doctors being over worked: 35.1% of sites reported having some kind of system (such as keeping slots free), although 59.3% stated that all patients without an appointment were seen.…”
Section: Discussionmentioning
confidence: 99%
“…A similar study carried out with 21 American sites showed an average appointment time of 20 minutes, varying between 15 and 40, for this type of appointment. 16 It is probable that, for some sites, the main problem is a lack of doctors, given the shortages and poor distribution of this professional, especially in public health services. Moreover, "squeezing in" patients who do not have appointments may contribute to doctors being over worked: 35.1% of sites reported having some kind of system (such as keeping slots free), although 59.3% stated that all patients without an appointment were seen.…”
Section: Discussionmentioning
confidence: 99%
“…Other programs have piloted innovative interventions to address human-resource challenges, including using peer health workers who are persons living with HIV, with support from higher-trained providers. 13,14 Other than the new patients, there seemed to be no specialization, as almost equal proportions of all categories of patients were seen by doctors and clinical officers or nurses. It is very unlikely that all categories of patients have the same clinical needs; the doctors at MMC and Mulago thought a significant proportion of the patients they saw did not need to be reviewed by doctors.…”
Section: Discussionmentioning
confidence: 99%
“…13,18,19,21,22 Youth-friendly locations were defined as clinics that were easily accessible by public transportation (0-0.5 miles) and HIV clinics that were co-located in buildings with multiple specialties that served the general population, which could offer greater acceptability, accessibility, and equitability for youth seeking confidential care in comparison to HIV clinics located in stand-alone buildings dedicated to HIV care.…”
Section: Methodsmentioning
confidence: 99%